The attitudes, role & knowledge of mental health nurses towards euthanasia because of unbearable mental suffering in Belgium: A pilot study - Demedts, Dennis; Roelands, Marc; Libbrecht, Julien; Bilsen, Johan (Journal of psychiatric and mental health nursing, 2018)
Accessible summary What is known about the subject? Euthanasia because of unbearable mental suffering (UMS euthanasia) has been legal in Belgium since 2002 under strict conditions of careful practice. UMS euthanasia occurs fairly rarely in Belgium, but the frequency has increased substantially over the past few years. Although most mental health nurses play an important role and are supportive of euthanasia in general, their role, attitude and knowledge when it comes to UMS euthanasia were unknown until now. What this paper adds to existing knowledge? Most mental health nurses in Belgium appear to be supportive towards UMS euthanasia and where UMS euthanasia is carried out, mental health nurses are often involved in the preceding decision‐making process. Mental health nurses critically reflect on the interpretation and application of the legal euthanasia criteria as experienced in their daily work with their patients, and identify several problems. After a rather quiet period in Belgium, the public ethical debate regarding UMS euthanasia has recently been reopened and intensified. What are the implications for practice? Sufficient attention must be paid to how mental health nurses can be involved in the process of UMS euthanasia. This applies at several levels: legal, healthcare policy, bedside care and education. Specific attention must be paid within the UMS euthanasia process to ensure adequate cooperation between physicians, nurses and patients. There is a need for proper training in: knowledge of psychiatric pathologies and remaining treatment options; communication skills; the legal framework and all its difficulties; transdisciplinary and multicultural approaches; ethical reflection and how nurses handle their own emotions. Introduction Euthanasia because of unbearable mental suffering (UMS euthanasia) has been legal in Belgium since 2002, under certain circumstances that govern careful practice. Despite the legal framework, there are specific difficulties and concerns regarding UMS euthanasia. Mental health nurses are often involved in the process, but little is known about their attitudes towards UMS euthanasia, their role and their knowledge. Aim To determine the attitudes, role and knowledge of mental health nurses regarding UMS euthanasia. Methods A cross‐sectional survey was performed at a convenience sample of four psychiatric hospitals in Belgium (n = 133) as a pilot study. Self‐administered questionnaires were provided to mental health nurses. Results Half the nurses in our sample had been involved at least once in the process of UMS euthanasia. A large majority of mental health nurses were supportive of UMS euthanasia. Nurses show differences in attitudes related to the different psychiatric pathologies of the patients, and in whether or not minors are involved. In some cases, they believed that the mental suffering of psychiatric patients can be unbearable and irreversible and that psychiatric patients can be competent to voluntarily request UMS euthanasia. Nurses stated that they have an important role in the UMS euthanasia process, but also demanded more knowledge and clear guidelines to implement the procedure. Discussion Nurses have a key role regarding UMS euthanasia but face several challenges: the recent process, resistance to a multidisciplinary approach by psychiatrists and an unclear role defined by the legal framework. Nurses do not appear to have a common voice on the topic and the development of clear guidelines appears to be essential. Social recovery can offer a way out of an UMS euthanasia request, but it will not always offer a solution. Implications for Practice Sufficient attention must be paid to how mental health nurses can be involved in the process of UMS euthanasia at various levels: bedside practice, healthcare management, education and policy. A form of systematic cooperation between nurses, physicians and patients can contribute to the utmost careful decision‐making process needed in these cases. There is a need for proper training in: knowledge of psychiatric pathologies and remaining treatment options; communication skills; the legal framework and all its difficulties; transdisciplinary and multicultural approaches; ethical reflection and how nurses handle their own emotions.